Identification of Thalassemia Disorder using Active Contour - Nurhanis Izzati Binti Che Marzuki Izzati Binti Che Marzuki; Nasrul Humaimi bin Mahmood Humaimi bin Mahmood; Mohd Azhar bin Abdul Razak (Institute of Advanced Engineering and Science, 2017)
Thalassemia was known as the red blood cell (RBC) morphology disorder. This disease mostly affects the shape of the red blood cells. Thalassemia becomes the major public health problem when one of the people becomes the carrier of the disease. It can occur within a months after birth or even before birth and results in inappropriate growth and development of babies. Sometimes the affected babies will die shortly after birth. In order to screen thalassemia, there are a few tests need to be done. Firstly by performed Complete Blood Count (CBC) and secondly continued with hemoglobin electrophoresis test. This CBC test will identify the morphology of RBC. Hence, this paper will discuss the methods on identifying the morphology of thalassemia blood cells by using active contour technique. From the result of 16 normal and abnormal blood cell images, the active countour methods able to identifyThalassemia blood cells with accuracy of 90% from the abnormal cell images.